Development of a novel near-infrared fluorescence light-up probe with a large Stokes shift for sensing of cysteine in aqueous solution, living cells and zebrafish. (December 2019) - Zhang, Xiaoyu; Liu, Heng; Ma, Yingying; Qu, Wangbo; He, Hanping; Zhang, Xiuhua; Wang, Shengfu; Sun, Qi; Yu, Fabiao
Abstract: As an important sulfur-containing amino acid, aberrant levels of cysteine are closely related with an array of dieases. Although many Cys-specific fluorescent probes have been designed, most of them wouldn't be able to detect Cys in buffer solution, which limits the application of the probe in biological system. In this work, a novel near-infrared fluorescent probe Cys-WR with a large Stokes shift (about 110 nm) was developed for the detection of Cys by conjugating the fluorophore WR-4 with crotonate moiety. The probe exhibited off-on response to Cys with wide linear range of 0–100 μM, as well as the color of the probe solution changes from deep pink to brown observed by naked eyes. Moreover, the probe showed little cytotoxicity. Imaging of Cys using this probe in living A549 cells and zebrafish had also been well demonstrated. Graphical abstract: Image 1 Highlights: A novel near-infrared fluorescent probe Cys-WR with a large Stokes shift was constructed for detection of Cys. The probe Cys-WR showed NIR off-on response to Cys with high sensitivity and selectivity. The probe Cys-WR can be employed to monitor exogenous and endogenous Cys fluctuation in living cells and zebrafish.